Budget balance: approaches to definition and estimation - M. N. Solomko (Вестник университета, 2019)
The challenges of local budgets’ balance have been examined. Budget defi it (budget surplus) is one of the main budget characteristics, and indicators of balance are included in the number of the indicators of financial stability of public legal entities. The overview of diff rent approaches to budget balance definition allowed to identify their relationship, including manifested in the system of indicators for assessing the quality of balance. Dynamics of absolute and relative indicators of balance of local budgets has been analyzed, the structure of sources of financing of their deficit has been considered, the conclusion about a significant role of measures of budgetary regulation in maintenance of balance of local budgets has been made. Additions to the existing approaches to assessing the quality of budget balance have been proposed.